Reactive Power/Voltage Control for Unbalanced Distribution System Using Genetic Algorithms - Ulinuha, A.; Masoum, Mohammad Sherkat; Islam, Syed (IEEE, 2014)
The unbalanced conditions are taken into account in the Reactive Power/Voltage control of distribution system. The aim of the control is to simultaneously minimize energy loss and improve voltage profile. The control is carried out by optimal dispatch of load tap changers (LTC) and shunt capacitors considering unbalanced conditions. A genetic algorithm (GA) is developed to determine the load curve partition for effective LTC scheduling and switching constraint satisfaction. GA is also appointed to determine the optimal dispatch schedule of the devices and to check the fulfillment of switching constraints prior to performing calculations. For power flow analyses under unbalanced conditions, a forward/backward propagation algorithm is developed. The optimization is implemented on the IEEE 34-bus unbalanced distribution system, and the presented system improvements are highlighted. The main contribution is inclusion of unbalanced system conditions into the optimal dispatch problem considering different daily load curves for the three phases of distribution system.